POSITION CONTROL OF BRUSHLESS DC MOTOR BASED ON DIGITAL SIGNAL PROCESSING - Gencer, Cetin; Coskun, Ismail (Pamukkale Univ, 2006)
Brushless DC Motors (BLDC) have been used widely high performance control systems which are depended on to development of power electronic and control technology. In these motors to fed commutated supply, the control of position without oscilation has been required. In this study, position control of BLDC with digital signal processing has been implemented by a proportional-derivative (PD) controller because of its simple structure. It has been seen that the controller which is proposed from simulation and experimental studies, has a quick dynamic responce with nonoscillation.
Keywords: Brushless DC motor; PI controller; Digital signal processing